Comparison of UV-C and thermal pasteurisation for the quality preservation of pineapple-mango juice blend - Kamarul Zaman, Amanina Amani; Shamsudin, Rosnah; Sulaiman, Alifdalino; Mohd Adzahan, Noranizan; Sulaiman, Alifdalino (Rynnye Lyan Resources, 2019)
Massive grow in the juice industry promotes the development of the new flavour juice by blending two or more different types of fruits. Application of ultraviolet-irradiation of light spectrum C (UV-C) on single juice already widely explored whereas limited study was done on juice blend. Thus, the effect of ultraviolet-irradiation (UV-C) on physicochemical and antioxidant properties of pineapple-mango juice blend was investigated. Pineapple and mango juice blended together at blending ratio of 70 pineapple: 30 mango (volume/volume). Physicochemical properties of pH, total titratable acidity, total soluble solid and turbidity of pineapple-mango juice blends UV-C (UV-C dosage of 8.38mJ/cm²) and thermally (90°C, 5 mins) treated were significantly changes (p<0.05) during 9 weeks of storage at 4°C. Antioxidant qualities namely ascorbic acid, total phenolic compounds (TPC), and total antioxidant (as DPPH assay scavenging activities) of UV-C treated pineapple-mango juice blend shows higher values throughout the storage period. A Pearson correlation showed that ascorbic acid is the main contributor in antioxidant properties of pineapple-mango juice blend as decreased in ascorbic acid content caused degradation in TPC during storage. Present study proved that UV-C treatment better in nutritional and heat sensitive component retention compared to conventional thermal pasteurisation.